IT IS FOR THE JURY TO DECIDE WHETHER THE HOMICIDE WAS MOTIVATED BY JEALOUSY AND WHETHER, IN THE CONCRETE CASE, SUCH SENTIMENT QUALIFIES THE CRIME (CIPEEX, 2025)
This study examines the role of the Jury in identifying jealousy as the motive for homicide and in determining its possible legal qualification. The introduction situates the issue in the Jury’s constitutional competence over intentional crimes against life and in the centrality of motive for sentencing. The aim is to outline criteria that guide decisions on when jealousy may, depending on the case’s circumstances, aggravate the offense and affect sentencing. The method is a doctrinal and case-law review, focusing on provisions of the Brazilian Penal Code, notably article 121 (qualifying circumstances) and article 59 (sentencing factors), together with the Jury’s decisional practice. The findings systematize that assessment is case-specific and evidence-driven: factual and psychological context, motives, and surrounding circumstances are weighed; jealousy may be treated as a base or futile motive—or, conversely, as mere passion—depending on the evidentiary set. It concludes that the decision lies with the Jury but requires reasoned grounding as to the offense’s objective and subjective elements, ensuring proportionality and coherence in the penal response.
Keywords: jury trial; jealousy; aggravated homicide; homicide qualifying circumstance